Dominant Position in the Aviation Industry: Case Analysis of Appointment of Strategic Business Partners (Wholesaler) By PT.Garuda Perspective UU No. 5 of 1999 - Abdullah Taufik (UIN Sunan Gunung Djati, 2023)
In 2019, PT. Garuda Indonesia (Persero) Tbk. introduced the Indonesian Jiddah flight route for Umrah services, employing a wholesaler mechanism through the appointment of strategic business partners. This exclusive arrangement limited Umrah ticket reservations to specific partners and raised concerns about PT. Garuda's potential dominance in the market, which could lead to violations of business competition laws. The aim of this research is to analyze PT. Garuda's behavior in appointing these strategic partners and assess its potential for abusing its dominant position. Additionally, it examines the authority of the Business Competition Supervisory Commission (KPPU) in addressing allegations of PT. Garuda's abuse of its dominant position and explores the broader implications of such abuse on market competition. This study employs a normative juridical approach, scrutinizing relevant statutory regulations and adopting both statutory and case approaches to provide insights into the market concentration and its potential impact on competition.